Pharmacogenomic Study Reveals New Variants of Drug Metabolizing Enzyme and Transporter Genes Associated with Steady-State Plasma Concentrations of Risperidone and 9-Hydroxyrisperidone in Thai Autism Spectrum Disorder Patients - Medhasi, Sadeep; Pinthong, Darawan; Pasomsub, Ekawat; Vanwong, Natchaya; Ngamsamut, Nattawat; Puangpetch, Apichaya; Chamnanphon, Monpat; Hongkaew, Yaowaluck; Pratoomwun, Jirawat; Limsila, Penkhae; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2016)
The present study sought to investigate the genetic variants in drug metabolizing enzyme and transporter (DMET) genes associated with steady-state plasma concentrations of risperidone among Thai autism spectrum disorder (ASD) patients. ASD patients taking risperidone for at least one month were enrolled for this pharmacogenomic study. Genotyping profile was obtained using Affymetrix DMET Plus array interrogating 1931 variants in 231 genes. Steady-state plasma risperidone and 9-hydroxyrisperidone were measured using liquid chromatography/tandem mass spectrometry (LC-MS/MS) assay. The final analysis included 483 markers for 167 genes. Six variants, ABCB11 (c.3084A>G, c.*420A>G, c.*368G>A, and c.*236G>A) and ADH7 (c.690G>A and c.-5360G>A), were found to be associated with plasma concentrations of risperidone. 9-Hydroxyrisperidone and the total active-moiety levels were associated with six gene variants, SCLO1B1 (c.-11187G>A and c.521T>C), SLCO1B3 (c.334G>T, c.699A>G, and c.1557G>A), and SLC7A5 c.*438C>G. Polymorphisms in UGT2B4 c.*448A>G and CYP2D6 (c.1661G>C, c.4180G>C, and c.-2178G>A) showed considerable but not significant associations with metabolic ratio. This pharmacogenomic study identifies new genetic variants of DMET genes in monitoring risperidone therapy.